The Value of ISBAR (Introduction,Background, Assessment and Recommendation) Handover in COVID-19 Pandemic and Non-COVID Clinical Practice in Improving Population Health: A Scoping Review of the Literature - Carlo Lazzari; Marco Rabottini (Current Innovations in Disease and Health Research Vol. 4, 2023)
Having reliable handovers during COVID-19 emergencies and highly diffusible infectious diseases helps reduce threats to population health. In this case, coordination between teams of different clinical practitioners through a shared handover framework helps diffuse knowledge and data to understand COVID-19 and non-COVID multifaceted medical conditions in patients and populations. However, one of the significant contributors to harmful clinical outcomes is a communication breakdown, especially when there is an interprofessional handover. The introduction, situation, background, assessment, and recommendation (ISBAR or simply SBAR) communication tool was created to improve handover efficiency and is commonly believed to enhance patient safety and quality of care. Summary of the effects of SBAR application on patient safety in both COVID-19 and non-COVID clinical settings are the primary objectives of this scoping review. It is also reported that communication bottlenecks occur when health professionals communicate more prevalently with co-workers from the same educational or professional background. In this case, information and knowledge about communal patients do not circulate consistently within interprofessional teams. The current chapter is a scoping review of articles published on I/SBAR during COVID-19 and non-COVID clinical practice completed using MEDLINE, PUBMED, EMBASE, CINAHL, Web of Science and Google Scholar. The search also included the SBAR (Situation, Background, Assessment and Recommendation) derivates such as ISBAR (Introduction + SBAR) and K-SBAR (Kindness + SBAR). All original articles fulfilling the eligibility criteria were included: (1) SBAR or ISBAR were used in handovers, (2) the studies were quantitative, qualitative or mixed methods with robust statistical background and outcome measures, (3) settings were nursing, pharmacy or medical schools.